Analisis Faktor Determinan Pengungkapan Sustainability Report (Studi Empiris pada Perusahaan yang Terdaftar dalam Indeks LQ–45 Tahun 2019 – 2022) - Novius, Andri (JAAMTER : Jurnal Audit Akuntansi Manajemen Terintegrasi, 2023)
This research aims to find out whether gender diversity, audit committees, institutional ownership, and employee pressure has a significant effect on the sustainability report. This research method is a quantitative research by taking samples using a purposive sampling technique based on predetermined characteristics of 20 companies listed in the LQ-45 index for 2019-2022. The type of data used is secondary data and the method of analysis used is panel data regression using Eviews. The results of the study show that the calculation of the hypothesis, namely gender diversity, has no significant effect on the sustainability report with a significant level of 0.5341> 0.05. The audit committee has no significant effect on the sustainability report with a significant level of 0.6224>0.05. Institutional ownership has no significant effect on the sustainability report with a significant level of 0.1466>0.05. Employee pressure has a positive and significant effect on the sustainability report with a significant level of 0.0105<0.05. For simultaneous testing, an F count of 3.812784 is obtained with a probability of 0.000022 <0.05, meaning that gender diversity, audit committee, institutional ownership, and employee pressure simultaneously influence the sustainability report.